Multifaceted Roles of Superoxide Dismutases (SODs) in Cellular Homeostasis and Cancer Progression: Redox Regulation and Therapeutic Implications: Superoxide Dismutases in Redox Regulation and Cancer Progression - Aydemir, Duygu; Ulusu, Nuriye Nuray (Journal of Medical Biochemistry, 2025)
Superoxide dismutases (SODs) are critical metalloenzymes involved in detoxifying reactive oxygen species (ROS), playing a pivotal role in maintaining redox homeostasis and cellular integrity. Comprising three isoforms—SOD1 (cytosolic Cu/Zn-SOD), SOD2 (mitochondrial Mn-SOD), and SOD3 (extracellular Cu/Zn-SOD)—these enzymes catalyze the dismutation of superoxide radicals into hydrogen peroxide and oxygen. Altered SOD expression and function are closely linked to cancer initiation, progression, metastasis, and therapy resistance. SOD1 and SOD2 promote tumor survival by regulating redox-sensitive signaling pathways, including MAPK, PI3K/Akt, and NF-κB. The mTORC1-SOD1 axis emerges as a key mediator of cancer cell adaptation to hypoxia and nutrient deprivation. SOD2 overexpression enhances redox signaling and tumorigenicity, while its inhibition sensitizes tumors to chemotherapeutic agents like 5-fluorouracil. SOD3, traditionally viewed as protective, shows dual roles depending on the cancer context, with implications in angiogenesis, metastasis, and prognosis. Moreover, synthetic MnSOD mimetics—such as Mn porphyrins, salens, and mitochondrial-targeted antioxidants—offer therapeutic potential by modulating oxidative stress in tumor microenvironments, acting as both radiosensitizers and radioprotectors. These findings highlight the multifaceted functions of SOD enzymes in cancer biology and underscore their value as diagnostic biomarkers and therapeutic targets in redox-based cancer treatment strategies.
Keywords: Superoxide dismutases, ROS, cellular homeostasis, cancer progression, redox regulation, ferroptosis, antioxidant systems, tumor microenvironment, oxidative stress, SOD1, SOD2, SOD3